Perlindungan Hukum Terhadap Distorsi Orisinalitas Ekspresi Budaya Tradisional Kesenian Jaran Kencak Lumajang - Rizki Hidayat; Rhama Wisnu Wardhana; Nuzulia Kumala Sari (Badan Strategi Kebijakan Hukum, 2026)
In the dynamics of contemporary societal development, Traditional Cultural Expressions (TCEs) frequently experience distortion in the form of shifts in cultural values and identities resulting from modifications that incorporate elements of modern culture. The Jaran Kencak performance art in Lumajang is one of the Traditional Cultural Expressions that has undergone distortion due to modifications in its musical accompaniment, accompanying dances, and performers’ costumes. This study aims to analyze the legal protection framework for preserving the originality of Jaran Kencak as a Traditional Cultural Expression and to examine the legal consequences of modifications that have caused distortion to Jaran Kencak as a Traditional Cultural Expression. This research employs a normative juridical method with conceptual and statutory approaches. The findings reveal that the legal protection framework for Jaran Kencak as a Traditional Cultural Expression and intangible cultural heritage encompasses preventive and negative protection, which positions the state as the primary guardian; defensive protection through inventory mechanisms as both a Traditional Cultural Expression and intangible cultural heritage; and repressive protection through dispute resolution and the imposition of administrative sanctions against its misuse. Furthermore, modifications to the music, dances, and costumes in Jaran Kencak performances have distorted its cultural identity as well as its aesthetic and social values. Such modifications are inconsistent with Law Number 28 of 2014 on Copyright, Law Number 5 of 2017 on Cultural Advancement, and Government Regulation Number 56 of 2022 on Communal Intellectual Property.